89Zr-labeled anti-endoglin antibody-targeted gold nanoparticles for imaging cancer: implications for future cancer therapy. (2014) - Karmani, Linda; Bouchat, Virginie; Bouzin, Caroline; Levêque, Philippe; Labar, Daniel; Bol, Anne; Deumer, Gladys; Marega, Riccardo; Bonifazi, Davide; Haufroid, Vincent; Michiels, Carine; Grégoire, Vincent; et al.
Aims: Antibody-labeled gold nanoparticles represent an attractive tool for cancer imaging and therapy. In this study, the anti-CD105 antibody was conjugated with gold nanoparticles (AuNPs) for the first time. The antibody biodistribution in mice before and after conjugation to AuNPs was studied, with a focus on tumor targeting.Materials & methods: Antibodies were radiolabeled with 89Zr before conjugation to AuNPs (5 nm). Immunonanoconjugates were characterized in vitro in terms of size, stability in plasma and binding to the target. Quantitative PET imaging and ICP-MS analysis assessed in vivo distribution and specific tumor targeting of tracers. Results: The tumor uptake of immunoconjugates was preserved up to 24 h after injection, with high tumor contrast and selective tumor targeting. No major tracer accumulation was observed over time in nonspecific organs. ICP-MS analysis confirmed the antibody specificity after nanoparticle conjugation.Conclusion: The anti-CD105 antibody conjugation to AuNPs did not greatly affect CD105-dependent tumor uptake and the efficacy of tumor targeting for cancer detection. Original submitted 29 April 2013; Revised submitted 20 September 2013